Percepção do cliente sobre a manutenção do relacionamento com fornecedores preferenciais de TI - Batista, Guilherme Henrique (Universidade do Vale do Rio dos Sinos, 2012)
The term relationship marketing was introduced in academic literature in late 70's as a corporate strategy to prioritize long-term relationships to obtain advantages and benefits. Since then, a series of dimensions are proposed in the literature to understand the maintenance of supplier relationship. With the growing number of available dimensions, it is more complex the understanding of which are the most important dimensions to be used in further researches and dimensions which are not as significant. This study suggests an approach of a quantitative-descriptive nature to verify the customer's perception concerning the maintenance of the relationship in the context of IT services. For such, were used high-order dimensions, which evaluated the relationship in general, with one-dimensional and multidimensional measures. Were highlighted by the study two dimensions of higher order found in the literature, which are the quality of relationship and the value of the relationship. Resulting from these dimensions it was used structural equation modeling to develop and test three theoretical models. One of the models used a mixed approach that sought to integrate the quality of the relationship and the value of the relationship. Data collection was carried out through a survey with 290 IT executives from companies located in the state of Rio Grande do Sul which buy and need IT services. The results suggest that the model that represents the quality of the relationship has higher position to assess the maintenance of the relationship of IT service suppliers. When the quality of relationship and value of the relationship are placed in a joint evaluation, the value of the relationship loses effect in relation to maintenance of the relationship. Other implications arising from of this analysis are commented and suggested as future researches.
Keywords: Qualidade do relacionamento; Valor do relacionamento; Manutenção do relacionamento; Serviços de TI; Relationship quality; Relationship value; Relationship maintenance; IT services; ACCNPQ::Ciências Sociais Aplicadas::Administração